The Role Of Natural Antioxidants In Delaying Premature Skin Aging Process - Maria Chatarina Indiradewi Hastiningsih (Jurnal EduHealth, 2025)
The process of premature aging of the skin is an inevitable biological phenomenon, characterized by changes in the structure and function of the skin due to internal factors (intrinsic) such as genetics and external factors (extrinsic) such as exposure to UV rays, pollution, and free radicals. This study aims to analyze the role of natural antioxidants in delaying the process of premature aging of the skin through the mechanism of protection against oxidative damage caused by free radicals. This research method uses a qualitative approach with a descriptive method with data sources in the form of literature reviews by examining various relevant scientific studies related to the study. The results of this study indicate that consuming foods rich in natural antioxidants plays a significant role in slowing the process of premature aging of the skin. Antioxidants such as vitamin C, vitamin E, flavonoids, and polyphenols have been shown to be effective in fighting free radicals, reducing inflammation, and repairing damage caused by exposure to UV rays and pollution. Research also reveals that antioxidants can help maintain skin moisture, reduce fine lines and wrinkles, and brighten dull skin. These results emphasize the importance of choosing a diet rich in antioxidants to maintain skin health and delay premature aging, strengthening the argument that skin care based on natural nutritional intake can provide long-term benefits for skin appearance .